Beyond the post-industrial city: Valuing and planning for industry in London. (November 2017) - Ferm, Jessica; Jones, Edward
This paper examines the challenges that planners face if industry is to survive and thrive in a growing 'post-industrial' city. It examines London, where the difference between the value of land for residential and industrial use, and the pressure to address the housing crisis, is leading to the rapid loss of industrial land and premises. The paper first explores the role of industry in a high-value city such as London, arguing that trends in manufacturing in advanced economies are increasing the benefit for firms of an urban location, whilst at the same time, cities continue to need industry if they are to be economically and socially resilient, sustainable and vibrant. The paper then explores current approaches to planning for industry in London, identifying impacts of a policy framework that anticipates and plans for its decline. Finally, it focuses on the question of how to plan for a productive and inclusive city: we explore the arguments in favour of integrating industry into the urban fabric as well as the benefits of separating land uses and retaining employment land designations, and reveal how urbanists are divided. We argue that if London is to continue to prosper, and meet the needs of all Londoners, then we need to strategically and proactively plan for industry in the city, to experiment with innovative ways of integrating it with other city uses, whilst protecting land for industry, where required. We put forward a critical research agenda to effectively meet this challenge in the future.